Sudan : Enhanced Heavily Indebted Poor Countries (HIPC) Initiative-Decision Point Document. (IMF Staff Country Reports; Country Report ;, 2021)
Sudan, with the support of the international community, is implementing an ambitious reform program to address major macroeconomic imbalances and support sustainable, inclusive growth. A new transitional government was established in the wake of the 2019 revolution with the mandate to carry out sweeping reforms to reverse decades of economic and social decline. The government is pursuing a transformational reform agenda focused on: (i) achieving internal peace based on inclusion, regional equity, and justice; (ii) stabilizing the economy and correcting large macroeconomic imbalances; (iii) providing a foundation for future rapid growth, development, and poverty reduction; and (iv) improving governance and transparency.